Rancang Bangun Aplikasi Penilaian Pelayanan Desa di Kantor Lurah Sei Agul Menggunakan Metode Service Quality - Vina Aulia Silalahi; Nidia Enjelita Br Saragih (Universitas Methodist Indonesia, 2025)
Public services at the village office level play a vital role in realizing good governance. However, many citizens still feel dissatisfied with the quality of services, particularly in terms of speed, accuracy, and staff attitude. Therefore, there is a need for a system that not only simplifies service application processes but also objectively evaluates Service Quality. This study aims to design and develop a web and mobile-based application that enables users to request services and provide feedback on Service Quality. The Service Quality (ServQual) method is used to measure the gap between citizens’ expectations and perceptions across five dimensions: Tangibles, Reliability, Responsiveness, Assurance, and Empathy. The result of this research is an application that facilitates easier access to public services and provides valuable insights for the village office to continuously improve Service Quality.